Novel oscillator based on voltage and current Gain adjusting used for control of oscillation frequency and oscillation condition - Sotner, R.; Jerabek, J.; Jaikla, W.; Herencsar, N.; Vrba, K.; Dostal, T. (My University, 2013)
The paper deals with novel controllable oscillator where two types of electronic control are used. Proposed second-order circuit contains current follower, adjustable current amplifier, adjustable voltage amplifier, two resistors and two grounded capacitors. Oscillation frequency is tuned by voltage gain of used voltage amplifier that is represented by high-frequency voltage-mode multiplier. Oscillation condition is automatically regulated by current gain of the adjustable current amplifier which is based on current-mode multiplier. Experimental results confirmed workability of the circuit.
Keywords: Adjustable; Adjustable voltage amplifier; Current amplifier; Current follower/inverter; Electronic control; Oscillator